COMPARISON BETWEEN THE CRIME OF DECEPTION AND THE CRIME OF INFLUENCE PEDDLING - Alexandru STAN (Challenges of the Knowledge Society)
The present article aims to analyse and comment on the problems generated both in theory and in judicial practice by the incidence of the crime of fraud or the crime of influence peddling. As it follows from the cited examples, the contradictory solutions pronounced before the new Criminal Code regarding the choice of the appropriate legal classification, between the two crimes analysed, did not disappear even after 2014. In this sense, we consider that this work is useful for theorists and practitioners, our aim is not only to present and analyse the controversial solutions, but also to propose solutions that, even if they are not fully taken up, can constitute a basis for discussion for future cases. As I have shown in the article, the establishment of the correct legal framework between the two facts provided for by the criminal law is essential, both for the legal order and for the repercussions it may have regarding the main procedural parties and subjects within the criminal process.